After-hours events at the National Museum of Scotland: a product for attracting, engaging and retaining new museum audiences?. Issue 11 (2nd June 2020) - Easson, Hilary; Leask, Anna
ABSTRACT: Cultural heritage is recognized as one of the major contributors to the economy and has traditionally been funded from the public sector. Operating in an increasingly competitive tourism environment, museums have moved away from their traditional role as collectors and conservators of artefacts of historical importance, to become more audience- focused visitor attractions. This obligation to meet the needs and wants of its visitors has resulted in an improved museum experience, where museums are increasingly offering specially curated after-hours event experiences to attract, engage and retain new audiences such as Generation Y. This research uses National Museums Scotland as a case study to apply audience development and visitor attraction management theories to explore the effectiveness of after-hours events in attracting, engaging and retaining new museum audiences. Following a comprehensive narrative literature review, it employs qualitative semi-structured interviews and a quantitative on-line self-completion survey to collect the necessary data. The research findings suggest that after-hours events have been successful in attracting and engaging new museum audiences and encouraging repeat visits, therefore achieving the event and museum objectives. It is also seen that products designed specifically for one new audience may have broader appeal in engaging with other new and established audiences.